SIFAT FISIK DAN MEKANIK KOMPOSIT SEMEN-CaCl2-AREN DENGAN VARIASI TEKANAN PENGEPRESAN - Dikdo Kus Indarto; Dody Ariawan; WR Wijang (Prosiding SNST Fakultas Teknik, 2010)
The aim of this research is to investigate bending strength values of arengata-cement composite that based on variation of pressing pressure at manufacture. The composite consists of randomized arengata fiber as filler/reinforced (80 mesh size) and portland cement (50% weight ratio)-CaCl2 (10% weight ratio) mixing as matrix. The bending strength was characterized by Universal Testing Machine and the bending specimens based on ASTM D3039. The bending strength have been measured as a function of variation pressing pressure (70 Kg/cm2, 76 Kg/cm2, 82 Kg/cm2 dan 88 Kg/cm2). The experiment  result indicate that  bending strength increase with the increase of pressing pressure. As the result, the highest bending strength (125, MPa) and density (1,57 gr/cm3) were reached at 88 Kg/cm2 pressing pressure and the lowest water absorption was reached at 88 Kg/cm2 pressing pressure. Based on Scanning Electron Microscop observation, composite with 88 Kg/cm2 pressing pressure shows a good bond between matrik and fibre. Keywords : aren-cement composite, weight fraction of CaCl2 and bending strength.